Mixed Matrix Polysulfone Membrane Entrapped With Silicon Dioxide And Polyvinylpyrrolidone For Oil Emulsion Removal - Hussain, Kharulnisa Nadiah (2014)
Membranes have been known widely to treat emulsified water. New membrane technology has been fabricated to overcome hydrophobic phenomenon that occurred during separation of oil emulsion. In this study, polysulfone (PSf) membranes were fabricated with silicon dioxide (SiO2) nanoparticles to modify the membrane morphology and polyvinylpyrrolidone (PVP) is added to avoid agglomeration as well as to maintain the stability of SiO2 on membrane’s surface via phase inversion. The aim for this research is to determine the membrane that could produce high flux and high rejection efficiency by manipulating several parameters such as concentration of PSf, SiO2 and PVP. As preliminary study, the result shows that each of the parameter affects the membrane physical characteristic such as pore size and distribution, membrane morphology and UF flux. Therefore, further studies have been done to investigate the relationship between each parameters and desired response, thus optimize the parameters by using response surface methodology (RSM) coupled with central composite design (CCD). The parameters has been varied from 13 to 17 wt.% of PSf, 1 to 3 g of SiO2/100 g of casting solution and 2 to 4 g of PVP/100 g of casting solution concentration respectively. It is found that PSf and PVP concentration have the greatest effect on pure water flux and pure water flux after washing.